Pendekatan Kolaboratif: Peran Guru Seni Tari dalam Meningkatkan Pembelajaran Seni Musik di SMK Asta Mitra Purwodadi - Irsyad Aldi Setyoaji; Nafik Salafiyah (Jurnal Riset Rumpun Seni, Desain dan Media, 2026)
This research aims to analyze the adaptive role of a dance teacher in teaching the subject of music art at SMK Asta Mitra Purwodadi, as well as identifying the patterns of collaborative approaches and the implementation of the Deep Learning strategy in the learning process. This phenomenon attracts researchers due to the case of a teacher teaching cross-disciplinary subjects, although still within the domain of the arts. This study employs a qualitative method using observation, semi-structured interviews, and documentation techniques. The main subject of this research is Bu Evi, a dance teacher who also serves as the music art instructor. The research results indicate that the non-specialist teacher (with a dance background) successfully overcomes limitations in teaching music by performing a role transformation into a facilitator focusing on expression, rhythm, and performance. The implementation of Deep Learning is realized effectively through a kinesthetic approach, where abstract music concepts (such as tempo and dynamics) are translated through body movement exploration, which is proven to increase student enthusiasm and understanding. Furthermore, the teacher implements a strategic collaborative pattern with the music extracurricular teacher, where responsibilities are divided between aspects of expression/movement and the deepening of theory/vocal technique, ensuring talented students still receive adequate technical development. Assessment focuses on performative aspects (expression, tempo, teamwork, and self-confidence). This research concludes that the teacher's professionalism and pedagogical creativity are the main keys to bridging competency gaps, while simultaneously ensuring the achievement of the goals of the Merdeka Curriculum in shaping student character and 21st-century skills.